2009
DOI: 10.1177/153244000900900305
|View full text |Cite
|
Sign up to set email alerts
|

Representation in U.S. Legislatures: The Acquisition and Analysis of U.S. State Legislative Roll-Call Data

Abstract: Roll-call data have become a staple of contemporary scholarship on legislative behavior. Recent methodological innovations in the analysis of roll-call data have produced a number of important theoretical insights, such as understanding the structure of congressional decisionmaking and the role of parties and ideology in Congress. Many of the methodological innovations and theoretical questions sparked by congressional scholarship have been difficult to test at the state level because of the lack of comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Somewhat surprisingly, the previous literature has not taken advantage of this unique research design, neglecting the effects of electoral institutions on particularism. Several recent works take advantage of the proliferation of online voting records and sophisticated webscraping techniques have reduced the costs of collecting comprehensive state-level data (Clark et al 2009; Shor et al 2010), but those focus on the effects of legislator demographic characteristics on bill initiation and policy success (Bratton and Haynie 1999; Whitby 2002) or the role of parties in state legislatures (Battista and Richman 2011; Jenkins 2008; Wright and Schaffner 2002). Examining a sample of 165,000 bills spanning 120 years in 13 different states, Gamm and Kousser (2010) identified a considerable amount of particularistic legislation and found that particularistic legislation was related to the level of party competition in the legislature, with one party dominance associated with more particularistic bills, and members’ salaries (with higher compensation associated with more particularistic bills).…”
Section: Electoral Institutions and The Personal Votementioning
confidence: 99%
“…Somewhat surprisingly, the previous literature has not taken advantage of this unique research design, neglecting the effects of electoral institutions on particularism. Several recent works take advantage of the proliferation of online voting records and sophisticated webscraping techniques have reduced the costs of collecting comprehensive state-level data (Clark et al 2009; Shor et al 2010), but those focus on the effects of legislator demographic characteristics on bill initiation and policy success (Bratton and Haynie 1999; Whitby 2002) or the role of parties in state legislatures (Battista and Richman 2011; Jenkins 2008; Wright and Schaffner 2002). Examining a sample of 165,000 bills spanning 120 years in 13 different states, Gamm and Kousser (2010) identified a considerable amount of particularistic legislation and found that particularistic legislation was related to the level of party competition in the legislature, with one party dominance associated with more particularistic bills, and members’ salaries (with higher compensation associated with more particularistic bills).…”
Section: Electoral Institutions and The Personal Votementioning
confidence: 99%
“…This study combines the natural experiment provided by state legislative term limits with the research design used by Rothenberg and Sanders (2000) and Jenkins, Carson, and Crespin (2005) to assess party influence in legislative decision making. Although scholars have long understood the value of using state legislatures as laboratories to test general theories of legislative behavior that have typically been developed in the context of the U.S. Congress, the lack of systematic data on various aspects of state legislative behavior has limited our ability to assess theories of parties in legislatures across different institutional settings (Clark et al 2009;Squire and Hamm 2005). The implementation of term limits provides an ideal case to investigate how legislative behavior changes when the electoral connection is severed through an exogenously imposed electoral rule.…”
Section: Research Design Data and Measurementmentioning
confidence: 99%
“…In addition, “bridge votes,” or those in which members voted on a bill with the exact same legislative language, were used to further place members—such as state house and state senate members—on the same common space . In these data, we add a set of chamber‐specific variables, described below, derived in part from the Representation in America's Legislatures (RAL) data (Clark et al ).…”
Section: Methodsmentioning
confidence: 99%